Vernakularisasi Al-Qur’an di Tanah Bugis: Tinjauan Metodologis Terjemahan Al-Qur’an Karya Anregurutta Muh. Yunus Maratan - Mursalim Mursalim; Abbas Abbas (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
This article aims to reveal the vernacular activities of the Koran in the South Sulawesi region through the work of Bugis scholars. The focus of this study is specifically on the work of Tafsir al-Qur'an Al-Karim bi al-Lugah al-Bugisiyah written by AG. Yunus Maratan by testing his methodology and dialectics within the framework of Bugis culture. By using a descriptive-analytic approach, this article shows the findings that this work is an attempt to bridge the al-Qur'an as an Arabic text with ordinary Bugis people who do not understand the original language of the Qur’an (Arabic), so that Al-Qur'an. Methodologically, the work is not a literary interpretation like mainstream tafsir literatures, but only as a translation work of the Koran that combines tarjamah lafziyah and tafsiriyah. This phenomenon also proves that the history of the spread of Islamic da'wah in the archipelago, especially in South Sulawesi, is very flexible by involving various local elements as a medium for preaching, including the vernacular of al-Qur'an. That is why the works of Bugis clerics and the cultural context of the community are intertwined in forming a local Islamic culture.